Karakter Janda Batak Hidup Dalam Lingkungan Heterogen Di Silencang Humbang Hasundutan Berdasarkan 1 Timotius 5:3-8 - Flesia Nanda Uli Boangmanalu; Lestari br. Silaban; Anessa Mei Pasaribu; Yubilate Chriswell Zebua (LPPM - STT Kadesi Bogor, 2024)
This article is based on the paradigm of lack of respect for women who are widows in society. Widows are considered weak individuals and unable to replace men's work in the household. But the reality is different for widows in Batak society. Widows in Batak society have a loyal character and have high hopes for their children. children as a means of restoring her widow status. The aim of this research is to get an answer to what extent the loyal character of Batak widows survives in a heterogeneous environment. The method used is descriptive qualitative, namely analyzing, comparing and concluding various opinions from source books/journals from various experts regarding the character of the loyal Batak widow. by exploring the characteristics of loyalty and courage of Batak widows, it contributes a positive paradigm towards women who have the status of widows in society, thereby providing a new perspective that better appreciates the role and contribution of widows in heterogeneous families and society.